Artificial Intelligence and the Future of Interpreting: Professional Interpreters’ Perspectives - Petrocheilou, Maria (International Journal of Language, Translation and Intercultural Communication, 2026)
Recent research suggests that 60% of jobs in advanced economies are at risk of being replaced by Artificial Intelligence (Howarth 2025). Interpreters and translators rank first among the top 40 occupations with the highest AI applicability score, with 98% of their work activities overlapping with frequent Copilot tasks that demonstrate relatively high completion and scope scores. However, tests conducted with Google’s GEMINI 1.5 Flash and 2.0 Flash confirm that AI translation continues to sacrifice accuracy, logical coherence, and contextual awareness (Pereira 2024a, 2024b). Similarly, following internal trials with Wordly, the World Health Organisation has decided to restrict the use of AI to internal meetings under strict human supervision. Against this backdrop, we conducted a survey with interpreters in Greece, Cyprus, and Italy to explore their perceptions of the profession’s future. The findings reveal widespread apprehension about the sustainability of interpreting as a career. At the same time, a number of respondents acknowledged that AI, if appropriately integrated, may support interpreters in their work and contribute to enhanced performance.